A method for the validation of measurements collected by different monitoring systems applied to aquaculture processing plants. (November 2022) - Barbaresi, Alberto; Agrusti, Miki; Ceccarelli, Mattia; Bovo, Marco; Tassinari, Patrizia; Torreggiani, Daniele
Abstract : In recent years, the agricultural sector has taken advantage of real time monitoring, particularly in delicate systems such aquaculture plants. In this context there is a need to develop integrated systems for sustainable production of both vegetable crops and fish. Since a monitoring system able to collect all the involved metrics is not available on the market, a specific monitoring system called ISMaCS (Integrated Smart Monitoring and Control System) has been designed and developed to collect and analyse relevant data. A method is proposed for the validation of the measurements collected by ISMaCS based on comparisons between the data series collected by investigated and reference sensors. Firstly, experiments has been carried out recording with sensors, parameters and an indicator, called Distance between Measurements (DbM) that has been defined and calculated. DbM has been compared to two thresholds to test the sensor reliability. The first, the Identical Reference Value (IRV) was based on the characteristics of the reference sensor, whilst the second, the Acceptability Reference Value (ARV), was selected on the basis of the precision required by the application. Specifically, DbM showed that if the precision of the investigated sensor was suitable for a specific application, it quantifies the reliability of the measurements and can be used as a tool to compare and rank different sensors measuring the same metrics. Highlights: A method for the experimental measurements validation is proposed. The indicator called Distance between Measurements (DbM) is used for the validation. DbM shows if the precision of a sensor is suitable for an experimental test. DbM can quantify, compare and rank different sensors measuring the same metrics. The method confirms the sensors used in SIMTAP project are validated and reliable.